2019
DOI: 10.1002/ejoc.201901170
|View full text |Cite
|
Sign up to set email alerts
|

Cobaloxime‐Catalyzed Hydrogen Evolution in Photoredox‐Facilitated Small‐Molecule Functionalization

Abstract: The development of efficient, mild, economical, and low‐waste processes is a cornerstone of sustainable chemistry. One such synthetic strategy that exemplifies these characteristics is the use of catalytic dehydrogenation in small‐molecule functionalization. This has been achieved in recent history through the use of photoredox catalysis in conjunction with cobaloximes, a class of catalysts that are capable of proton reduction. This has allowed for a variety of bond formations to be achieved with few to no sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 114 publications
2
53
0
1
Order By: Relevance
“…In approaching this blueprint for α‐anilinoalkyl radical generation, we envisaged its utilization to target the still elusive demethylation of N‐methyl anilines (Scheme 2 B). Specifically, we proposed the development of a dual photoredox‐cobalt [12] catalytic system where a visible light‐excited [Ir III ] photocatalyst would, helped by the amine, generate D by oxidation and deprotonation of 2 while minimizing BET [13] . As D is a nucleophilic radical (local electrophilicity index, [14] ω + rc =0.36), we speculated it could react with a [Co II ] co‐catalyst and undergo dehydrogenation to give a [Co III ]‐H species and imine 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In approaching this blueprint for α‐anilinoalkyl radical generation, we envisaged its utilization to target the still elusive demethylation of N‐methyl anilines (Scheme 2 B). Specifically, we proposed the development of a dual photoredox‐cobalt [12] catalytic system where a visible light‐excited [Ir III ] photocatalyst would, helped by the amine, generate D by oxidation and deprotonation of 2 while minimizing BET [13] . As D is a nucleophilic radical (local electrophilicity index, [14] ω + rc =0.36), we speculated it could react with a [Co II ] co‐catalyst and undergo dehydrogenation to give a [Co III ]‐H species and imine 4 .…”
Section: Methodsmentioning
confidence: 99%
“…The ability to engage substrates containing electron poor arenes is remarkable since BET from their corresponding aminium radicals is accelerated. [8,21] meta-Substitution was evaluated next and electronically different functionalities were tolerated albeit in lower yield in the case of electron poor systems (12)(13)(14)(15). We then trialled ortho-substituted aromatics and also in this case very high yields were obtained across a broad range of derivatives (16)(17)(18)(19)(20)(21)(22).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Early examples of such transformations are based on the use of equimolar amounts of chemical oxidants, which is not ideal with respect to sustainability, safety, and functional-group tolerance. Oxidative couplings that occur under the concomitant evolution of hydrogen gas (CCHE) have emerged as a more advanced technology in this context [44][45][46][47][48]. While the proof-of-concept study on CCHE employed a heterogeneous graphene-supported ruthenium oxide nanocomposite for the hydrogen evolution [49], it was quickly demonstrated that cobaloxime derivatives are able to play the same role under homogeneous conditions (vide infra).…”
Section: Cchementioning
confidence: 99%
“…Finally, this key intermediate can be easily protonated to restore the Co III co‐catalyst along with H 2 gas evolution (Co III –H + H + → Co III + H 2 ). Such mechanistic scenario is particularly suited to realize photocatalytic net‐oxidative processes, where the oxidation states of the Co center spans from Co I to Co III , while Co 0 is never involved …”
Section: Catalytic Cycle Being Closed By a Co‐catalystmentioning
confidence: 99%